A compact and high sensitive photometer based on axial multi-reflection inside metal capillary: Application to detecting nitrite of nanomolar concentration. (November 2021) - Li, Xuejing; Huang, Hui; Cai, Weicheng; Bai, Min; Zhao, Jian; Liu, Pengbo; Sun, Changkai; Jin, Zengbin
Highlights: Axial back-and-forth-reflection (BFR) inside capillary was investigated. A photometer based on axial -BFR inside capillary was proposed. Optical-path enhancement of axial -BFR is more efficient than that of radial -BFR. In comparison with radial -BFR, axial -BFR features low transmission loss. The photometer features high sensitivity, compact, low cost and easy fabrication. Abstract: As for photometry analysis, increasing the optical-path (OP) via multi-reflection is an effective method for improving the detection sensitivity. In this paper, a photometer based on axial multi-reflection between two end-faces of capillary was proposed and investigated. The probe light can be back and forth reflected inside the capillary, by employing apertured silver-mirrors at both ends of a metal-capillary. With designed aperture profile (i.e., a central disc-aperture and a peripheral ring-aperture) of the mirror, a 4.2-fold enhancement on OP was realized (i.e., OP is 4.2 times the capillary length). Moreover, the photometer was applied to detecting nitrite with a detection limit of 1 nM, which exhibits 8.6~15 fold improvement compared with that of previous photometers with similar capillary length and the same chromogenic reagent without sample enrichment. The photometer features compact, low cost and easy fabrication.